Rayleigh‐Instability‐Induced Transformation for Confined Polystyrene Nanotubes Prepared Using the Solvent‐Vapor‐Induced Wetting Method - Zhi‐Xuan Fang; Chien‐Wei Chu; Chia‐Chan Tsai; Chun‐Wei Chang; Ming‐Hsiang Cheng; Chia‐Chih Chang; Jiun‐Tai Chen (Macromolecular Materials and Engineering)
Abstract Polystyrene (PS) nanotubes prepared using the solvent‐vapor‐induced wetting method with anodic aluminum oxide templates are for the first time applied to study the thermal stabilities of polymer nanotubes confined in cylindrical geometries. The morphologies of the PS nanotubes and the corresponding transformed PS nanostructures driven by the Rayleigh instabilities after thermal annealing treatments are characterized by scanning electron microscopy. Morphology diagrams of the Rayleigh‐instability‐induced nanostructures for PS nanotubes prepared via the solvent‐vapor‐induced wetting method and the solution wetting method are constructed to study the differences in kinetics for samples using different wetting methods. Slower transformation kinetics for the PS samples prepared by the solvent‐vapor‐induced wetting method than those prepared by the solution wetting method are observed, indicating the better thermal stabilities and the relatively denser packings of the polymer chains in the nanopores for the PS samples prepared using the solvent‐vapor‐induced wetting method.